Nonlinear Vibration of Nanocomposite Multilayer Perovskite Solar Cell in Thermal Environment - Dinh Khoe, Vu; Minh Phuong, Pham; Van Thanh, Nguyen; Quoc Quan, Tran; Dinh Duc, Nguyen (VNU Journal of Science: Mathematics - Physics, 2022)
In this work we investigated the nonlinear vibration of nanocomposite multilayer perovskite solar cell (NMPSC) subjected to the combination of mechanical and thermal loadings. The model of organic solar cell is assumed to consist seven functional layers: Au, Spiro-OMeTAD, PEDOT:PSS, Graphene oxide, MAPbI 3 , TiO 2 and IOT, and glass substrate. The governing equations are established basing on the classical plate theory taking into account the effect of elastic foundations and initial imperfection. Four edges of the NMPSC are assumed to be supported immovably in a transverse plane. The relationship between deflection amplitude and time as well as the expression of natural frequency of NMPSC are obtained by using the Galerkin and Runge – Kutta methods. The numerical results showed that the nonlinear dynamic response and the natural frequency of NMPSC have been strongly influenced by the geometrical and material parameters, initial imperfection, temperature increment and elastic foundations.   Keywords: Perovskite solar cell; nonlinear vibration; elastic foundations; initial imperfection; thermal environment